Foreign Currency Deposits : Implications for Macroeconomic Policies - Georgiou, Andreas (IMF Working Papers; Working Paper ;, 1991)
This paper discusses the relationship between foreign currency deposits and money, and it shows that the indexation of part of the nominal money supply to the exchange rate, as a result of the presence of foreign currency deposits, will increase the inflationary effects of monetary disequilibria under a floating exchange rate system and will reduce the effect of a devaluation of a usually fixed exchange rate. When a real exchange rate rule is followed, the presence of foreign currency deposits implies that there is less of a tradeoff between the rate of nominal depreciation/inflation and the level of the real exchange rate. The paper shows how certain aspects of financial programming may be affected by the presence of these deposits.